ANGGARAN DASAR YANG TIDAK SESUAI DENGAN PASAL 157 AYAT (4) UNDANG-UNDANG NO. 40 TAHUN TENTANG PRSEROAN TERBATAS - Nana Eka Wijayanti; Sumriyah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
In implementing national economic development, society is the main actor, and the Government is obliged to direct, guide and create a supportive atmosphere. Limited Liability Company, hereinafter referred to as Persero, is a legal entity in the form of a capital partnership, which is established based on an agreement, carrying out business activities with authorized capital which is entirely divided into shares. The articles of association serve as guidelines for running a company. Limited liability companies must determine their articles of association in accordance with UUPT 40/2007 so as not to cause problems for interested parties. Problem Formulation 1. What are the legal consequences for Limited Liability Companies whose articles of association do not comply with UUPT 40/2007? 2. Who is meant by an interested party in the explanation of article 157 paragraph (4)? The purpose of this research is to find out what legal consequences will arise if it is not in accordance with the PT's articles of association based on the PT UUPT and to find out who is meant by interested parties in the explanation of article 157 paragraph (4). In this journal, normative legal research methods are used with the scope of the articles of association of a company. The final result of this journal is the legal consequences if the articles of association are not in accordance with UUPT 40/2007, namely that all legal actions carried out by the PT are considered invalid because they contain formal defects, namely they are not in accordance with applicable law and can be dissolved. The parties interested in the explanation of article 157 paragraph (4) are Notaries, Shareholders, Prosecutors, Bank.